Third Five Year Plan Punjab State (List of Schemes Included in Third Five Year Plan with Main Targets) for 1961-66 - Planning Commission (Planning Commission, 1961)
Abstract Statement I showing sub-head-wise allocations of Third Five-Year-Plan, 1961-62 Sub-head of Development. Agricultural Production Head. Animal Husbandry. Head. Dairying and Milk Supply (Rupees in lakhs) Head. Forest. Head-Re-settlement of landless Agricultural Works.
The Planning Department Punjab State